2023
DOI: 10.7554/elife.86182
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the genetic and chemical basis of sexual attractiveness in parasitic wasps

Abstract: Attracting and securing potential mating partners is of fundamental importance for reproduction. Therefore, signaling sexual attractiveness is expected to be tightly coordinated in communication systems synchronizing senders and receivers. Chemical signaling has permeated through all taxa of life as the earliest and most widespread form of communication and is particularly prevalent in insects. However, it has been notoriously difficult to decipher how exactly information related to sexual signaling is encoded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…34−36 It would be helpful to improve the applications of parasitoids for biocontrol by clarifying their chemical perception process during mate finding, host location and oviposition. 31,34,37 For this reason, the olfactory communication mechanism of parasitic wasps has gradually received increased amounts of attention. 31,34−37 For example, previous studies have shown that AjapOR35 mediates the attractiveness of β-caryophyllene and (E)-α-farnesene to Anastatus japonicusis; 34 CchlOR62 participates in the detection of the female wasps attractant cis-jasmone in Campoletis chlorideae; 35 and CcunOBP2 has strong binding affinity for the parasitoid attractant 3-carene in Chouioia cune.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34−36 It would be helpful to improve the applications of parasitoids for biocontrol by clarifying their chemical perception process during mate finding, host location and oviposition. 31,34,37 For this reason, the olfactory communication mechanism of parasitic wasps has gradually received increased amounts of attention. 31,34−37 For example, previous studies have shown that AjapOR35 mediates the attractiveness of β-caryophyllene and (E)-α-farnesene to Anastatus japonicusis; 34 CchlOR62 participates in the detection of the female wasps attractant cis-jasmone in Campoletis chlorideae; 35 and CcunOBP2 has strong binding affinity for the parasitoid attractant 3-carene in Chouioia cune.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, reverse chemical ecology has been widely used for investigating the molecular mechanisms underlying the role of olfactory genes in various life activities in arthropods, especially in insect pests; however, such studies are relatively scarce in parasitic wasps. Parasitic wasps play a critical role in maintaining ecosystem stability, and most parasitic wasps are important natural enemies used for pest control. It would be helpful to improve the applications of parasitoids for biocontrol by clarifying their chemical perception process during mate finding, host location and oviposition. ,, For this reason, the olfactory communication mechanism of parasitic wasps has gradually received increased amounts of attention. , For example, previous studies have shown that AjapOR35 mediates the attractiveness of β-caryophyllene and (E)-α-farnesene to Anastatus japonicusis; CchlOR62 participates in the detection of the female wasps attractant cis -jasmone in Campoletis chlorideae; and CcunOBP2 has strong binding affinity for the parasitoid attractant 3-carene in Chouioia cune . In addition to plant or insect host volatiles, the interactions between MpulOBP6 of Meteorus pulchricornis and three insecticides were also investigated recently .…”
Section: Discussionmentioning
confidence: 99%
“…S1). Since these genes may be involved in fatty acid synthesis as such, in CHC synthesis, or both, it is crucial to validate the function of each gene via functional assays (Moris et al, 2023;Sun et al, 2023). Here, the varying gene family evolution across species, especially differences in gene expansion, combined with the yet unknown function of many of those genes might explain why our candidate list, which mainly includes solitary insects, likely does not cover the full set of CHC synthesis genes in our ant species.…”
Section: Cuticular Hydrocarbon Candidate Gene Expressionmentioning
confidence: 99%
“…Despite their considerable informative potential on direct links between genetic and CHC variation, studies comparing gene transcript counts or gene expression data with CHC profile complexity are largely lacking so far (Buellesbach et al., 2022 ; Holze et al., 2021 ). Most studies on CHC genetics either establish direct functional links between CHC biosynthesis genes and CHC variation through targeted knockdowns (Chung et al., 2014 ; Dembeck et al., 2015 ; Sun et al., 2023 ) or investigate the general genetic architecture underlying CHC compounds as quantitative traits (Buellesbach et al., 2022 ; Foley & Telonis‐Scott, 2011 ; Niehuis et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%